Islamic Party Survives in 2014 Legislative Election? (The Case of PKS) - Ahmad Ali Nurdin (UIN Sunan Gunung Djati Bandung, 2014)
This paper examines performances of PKS in the last 2009 election, West java and DKI Jakarta gubernatorial elections and the current 2014 legislative election to answer whether PKS looses or survives their political support from Indonesian people in the 2014 election. Although the cadres of PKS is still solid compare to that of other parties, there are a variety of reasons why the popularity of PKS slightly declined in the 2014 election compared to that of 2009 election. The involvement of the former president of PKS, Luthfi Hasan Ishak, in the case of beef graft has lessened the confidence of Indonesian people to the integrity of PKS in eradicating corruption in Indonesia. Thus, many Indonesians have doubt and less confidence in the capacity of PKS to solve other national problems. In addition, the weak and the least possible figure of PKS to be nominated as a president candidate is another reason why PKS cannot become a champion in the 2014 presidential election. Looking at the quick count result done by several survey institutions, however, PKS is considered to be survived in the 2014 election. They successfully maintain and strengthen their cadres’ solidity. Their leading figures were quite successful in rebuilding trust not only for their loyal cadres but also public in general that they are really ‘clean’ and ‘professional’ and ready to combat corruption in the country. PKS proved to the public that the case of their former president was ‘the only corruption case’ done by ‘personally individual’ (oknum) whom they will not tolerate.